Implementasi Prophetic Leadership di MI Nurul Ulum Bantul - Askina Nurani Syams (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2018)
Prophetic leadership is a leadership model based on the exemplary behavior of Prophet Muhammad SAW. It belongs to one of needed things in leading an Islamic school because an Islamic school leader should have spiritual values based on Islamic law. The implementation of prophetic leadership concept can be done by imitating the four characters of Prophet Muhammad SAW, namely: shidiq, âmanah, tablīgh, and faţânah. The implementation of prophetic leadership makes the leaded human resource in line with the leader desire in achieving common goals. The aim of this study is to describe the implementation of prophetic leadership model in MI Nurul Ulum Bantul. The research result shows that the implementation of prophetic leadership model in MI Nurul Ulum Bantul was done by imitating the four characters of Prophet Muhammad SAW, namely: shidiq, âmanah, tablīgh, and faţânah. Consequently, its implementation led to a positive effect, in which the teachers were in line with the wisdom made by the chief of MI Nurul Ulum Bantul.